Study on the behavior of micromilling process with the validation of finite element method - Nurul Hasya, Md Kamil (2025)
Micromilling is a precise and versatile machining process used to fabricate intricate and high-precision components with features often smaller than a millimeter. While previous studies have explored micromilling processes, there remains a significant gap in understanding the relationship between tool diameter variations and machining performance across different materials. Existing research has primarily focused on either tool wear or cutting parameters independently, without comprehensively examining how tool diameter affects both the mechanical and thermal aspects of micromilling. Additionally, while finite element analysis (FEA) has been used in machining studies, its accuracy in predicting micromilling behavior across different tool diameters and materials needs further validation. The objectives of the research are (1) to analyze the micromilling process using finite element analysis (FEA) to predict cutting forces, temperature distribution, and chip formation for tool diameters ranging from 0.3 to 0.9 mm when machining aluminium and mild steel, and (2) to validate these simulations through controlled machining tests, measuring cutting forces and surface quality to establish the accuracy of the FEA predictions. Aluminium Al6061 and mild steel AISI1045 were selected as test materials due to their contrasting properties and widespread industrial use. Al6061's excellent machinability and low hardness (107 HV) versus AISI1045's higher hardness (200 HV) provides an ideal comparison to evaluate tool performance across different material characteristics. These materials also represent common choices in aerospace and general manufacturing applications, making the findings particularly relevant for industrial applications. The study focused specifically on tool diameters between 0.3 and 0.9 mm, operating at speeds between 5,000 and 20,000 RPM, with feed rates ranging from 10 to 400 mm/min. The investigation was limited to dry machining conditions and straight-slot cutting operations, examining both the mechanical aspects (cutting forces, tool wear) and thermal effects during the micromilling process. The methodology employed a comprehensive two-phase approach combining FEA simulations using SFTC DEFORM 2D software with experimental validation using a high-speed machining setup. The results demonstrated that FEA simulations achieved accuracy rates of 84.18% for aluminium at higher feed rates (400 mm/min) with 0.9 mm tools, while accuracy decreased to 73.97% for smaller tools (0.3 mm). For mild steel, simulation accuracy varied more significantly, with error rates up to 83.89% depending on cutting conditions. Tool diameter significantly influenced cutting forces, with larger tools (0.9 mm) showing 45% lower cutting forces per unit thickness compared to smaller tools (0.3 mm) when machining aluminium. The simulations provided accurate estimates of cutting forces aligning closely with the experimental findings, particularly for larger tool diameters and aluminium workpieces. It was observed that machining aluminium and steel poses distinct challenges, primarily due to the higher hardness and toughness of steel and low heat capacity for aluminium, which leads to complex machining behavior and increased cutting forces.